A fast digital fuzzy logic controller: FPGA design and implementation - Nenedakis, F. I.; Tzafestas, Spyros G.; Deliparaschos, Kyriakos M. (My University, 2005)
This paper describes an improved approach to design a Takagi-Sugeno zero-order type fast parameterized digital fuzzy logic controller (DFLC) processing only the active rules (rules that give a non-null contribution for a given input data set), at high frequency of operation, without significant increase in hardware complexity. To achieve this goal, an improved method of designing the fuzzy controller model is proposed that significantly reduces the time required to process the active rules and effectively increases the input data processing rate. The DFLC discussed in this paper achieves an internal core processing speed of at least 200 MHz, featuring two 8-bit inputs and one 12-bit output, with up to seven trapezoidal shape membership functions per input and a rule base of up to 49 rules. The proposed architecture was implemented in a Field Programmable Gate Array (FPGA) chip with the use of a very high-speed integrated-circuits hardware-description-language (VHDL) and advanced synthesis and place and route tools.
Keywords: Digital fuzzy logic controller (DFLC); Hardware complexity; Internal core processing; Computer hardware; Data processing; Field programmable gate arrays (FPGA); Formal languages; Fuzzy sets; Natural frequencies